Where the jobs are. - Kariya, S. (IEEE spectrum)
Despite the avalanche of layoffs in assorted industries, elsewhere things are booming for electrical engineering, including defense, health care, and patent-related fields. According to the US Bureau of Labor Statistics, recent graduates with bachelor's degrees in electrical engineering should be greeted by a favorable job market this year. Looking ahead, the bureau further predicts overall demand for electrical engineers to remain strong, with EE employment rising 26 percent and 93000 new positions added over the decade ending in 2008.The prognosis for 2002 is not all bad for EE employment